Macro-anatomy of Radius and Ulna in Indian Wildcat (Felis lybica ornata) - Palanisamy, Dharani (Indian Journal of Veterinary Anatomy, 2018)
Radius was a rod-shaped bone with a shaft and two extremities. Bicipital tuberosity was rough tubercular present on proximal part of the posterior surface and towards the lateral border. Proximal extremity had concave facet circumscribed by a bony rim which was sharp and prominent in its lateral part. The styloid process was placed medially, which was prominent distally. Ulna was longer and heavier than the radius and located medio-laterally to radius. The proximal extremity of ulna had an olecranon process, an anconeus and trochlear notch for trochlea of humerus. The olecranon process was well developed with trifid summit. The distal extremity was much smaller than the proximal and was consisted of the styloid process laterally and one small convex facet for ulnar notch of radius.